Tests of Bias in Log-Periodogram Regression - James E. H. Davidson; Philipp Sibbertsen (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2005)
This paper proposes simple Hausman-type tests to check for bias in the log-periodogram regression of a time series believed to be long memory. The statistics are asymptotically standard normal on the null hypothesis that no bias is present, and the tests are consistent. The use of the tests in conjunction with tests of significance of the long memory parameter is illustrated by Monte Carlo experiments. – – Diese Arbeit schlgt einfache Hausman Tests vor, die auf Verzerrung der Log-Periodogrammregression bei Zeitreihen, die möglicherweise langes Gedächtnis haben, testen. Die Teststatistiken sind unter der Nullhypothese, dass keine Verzerrung vorliegt, asymptotisch standardnormalverteilt. Sie sind zudem konsistent. Der Nutzen der Tests in Verbindung mit Tests auf die Signifikanz des Gedächtnisparameters wird in einer Monte Carlo Studie dargelegt.
Keywords: C22; C12; 330; Long memory; log-periodogram estimation; Hausman test